LEADERSHIP EFFECTIVENESS DURING THE COVID-19 EPIDEMIC: CONFIRMATION OF JOB SATISFACTION FOR MANUFACTURING EMPLOYEES IN INDONESIA - Ahmad -Ahmad (Jurnal Ekonomi, 2023)
The purpose of this study is to confirm effective leadership during the 2019 coronavirus disease (COVID-19) epidemic, effective leadership is leadership that all organizations need. Maintaining and providing job satisfaction for employees during epidemic conditions. This study investigates three objectives; first, examine the direct effect of effective leadership on job satisfaction and OCB, second, examine the relationship between job satisfaction and OCB; and, third, investigate the mediation of the relationship between job satisfaction and OCB through effective leadership among employees and managers in private manufacturing companies in Indonesia. The research applies a quantitative approach using a questionnaire technique, data management applies structural equation modeling (SEM) techniques. Sampling using a simple random technique of employees who occupy managerial positions of 400 people to be analyzed. The results explain a significant relationship between effective leadership on job satisfaction and OCB, then, job satisfaction explains a positive correlation relationship with OCB. The moderating and mediating effect of effective leadership has a positive and significant association with job satisfaction and OCB. Private manufacturing companies in Indonesia are economically disadvantaged by non-natural disaster conditions which make it difficult to control conditions. This encourages companies to reduce spending by reducing the number of workers, production, and operations. Employees who feel aggrieved by management's decisions need solutions to remain in their jobs. This research shows that effective leadership can link employees to stay in position and improve overall organizational performance.